Rethinking Producer Liability in Autonomous Vehicle Accidents: Civil Law Causation Theories in Indonesia and Kuwait - Ardi, Rama Novtian; Al-Fahad, Hamad (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Regulations regarding autonomous vehicles have not yet been comprehensively regulated in various countries, particularly Indonesia and Kuwait.Purposes of the Research: Analyzing manufacturer liability in autonomous vehicle accidents in relation to civil law causality theory in Indonesia and Kuwait.Methods of the Research: Normative legal research with conceptual, comparative and legislative approaches.Results / Main Findings / Novelty/Originality of the Research: This study shows that the absence of explicit regulations regarding autonomous vehicles in the Traffic and Road Traffic Law creates uncertainty and potential injustice in determining the responsible subject and the applicable liability regime in the event of an accident, because the normative construction that still centers on the figure of the human driver is no longer adequate to respond to the complexity of decision-making by artificial intelligence systems. On the other hand, a comparative analysis of Indonesia and Kuwait shows that the causal relationship between the actions or negligence of manufacturers and the losses of victims of autonomous vehicle accidents has not been constructed in traffic law, but has been allowed to shift to the realm of general civil law and the product defect regime, so that the theory of civil law causality functions outside the framework of traffic law to assess whether the design, production, or failure of warnings by manufacturers is a sufficient cause of the victim's losses. Thus, this study emphasizes the urgency of adjusting, reinterpreting, and establishing specific regulations regarding autonomous vehicles that explicitly regulate manufacturer responsibility and clarify the construction of causality, so that legal protection, certainty of the rights and obligations of the parties, are guaranteed as autonomous vehicle technology develops.